The Use of Color Duplex Ultrasound for Local Perforator Flaps in the Extremity - Hong, Joon Pio; Hur, Joon; Kim, Hyung Bae; Park, Changsik John; Suh, Hyunsuk Peter (Journal of Reconstructive Microsurgery, 2021)
Background The local flaps, especially perforator and keystone flaps, are used as first-line treatment option in reconstruction of small tomoderate-sized defect of the extremity. However, the high complication rate associated with these flaps may hinder this usage.Methods This article reviews the technical and clinical aspect of using color duplex ultrasound )CDU) in the preoperative, intraoperative, and postoperative period for propeller and keystone flaps.Results CDU allows the surgeon to understand the anatomical aspect of the perforator such as the location, point of penetration on the deep fascia, subcutaneous pathway )axiality) and physiological aspect such as velocity and flow volume. Understanding and utilizing this information will allow accurate preoperative design, intraoperative decision making, and postoperative monitoring, leading to better outcome.Conclusion Carefully designed local perforator flaps based on anatomy and physiology using CDU will be a powerful armamentarium for reconstruction of the lower extremity.
Keywords: color duplex ultrasound; local flaps; perforator flaps